Dysphagia, dystussia, and aspiration pneumonia in elderly people - Ebihara, Satoru; Sekiya, Hideki; Miyagi, Midori; Ebihara, Takae; Okazaki, Tatsuma (Journal of Thoracic Disease, 2016)
Despite the development and wide distribution of guidelines for pneumonia, death from pneumonia is increasing due to population aging. Conventionally, aspiration pneumonia was mainly thought to be one of the infectious diseases. However, we have proven that chronic repeated aspiration of a small amount of sterile material can cause the usual type of aspiration pneumonia in mouse lung. Moreover, chronic repeated aspiration of small amounts induced chronic inflammation in both frail elderly people and mouse lung. These observations suggest the need for a paradigm shift of the treatment for pneumonia in the elderly. Since aspiration pneumonia is fundamentally based on dysphagia, we should shift the therapy for aspiration pneumonia from pathogen-oriented therapy to function-oriented therapy. Function-oriented therapy in aspiration pneumonia means therapy focusing on slowing or reversing the functional decline that occurs as part of the aging process, such as “dementia → dysphagia → dystussia → atussia → silent aspiration”. Atussia is ultimate dysfunction of cough physiology, and aspiration with atussia is called silent aspiration, which leads to the development of life-threatening aspiration pneumonia. Research pursuing effective strategies to restore function in the elderly is warranted in order to decrease pneumonia deaths in elderly people.